Christian attitudes in scholarship: The role of worldviews - Coletto, Renato (Koers, 2012)
This article starts from the realisation that a few different approaches to science and scholarship are implemented within different Christian traditions. In an attempt at identifying the reasons behind such differences, it is argued that the approach to science and scholarship adopted in each Christian tradition corresponds to a considerable extent to the worldview accepted in that tradition. In this article, several versions of the main Christian worldviews are identified and related to the work of authors (e.g. Murphy, the Theonomic movement, Barbour, Van Huyssteen, Wolterstorff) who were not discussed in previous works on this topic. The possibility of ‘mixing’ the worldviews (thus adopting an eclectic approach) is also discussed. The proposed taxonomy may be used to understand at a deeper level both individual authors and trends, and also to sketch a ‘map’ of the different movements, contributors and available options. It is argued that the different worldviews are not equally valuable and that the reformational worldview should be regarded as more integrally and originally biblical. The article ends with a call to consistency for the sake of sound Christian scholarship.